The Influence of Age on Eye Movements during Reading in Early Elementary School Children - Wertli, Jason; Schötzau, Andreas; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose Eye movement disorders have been observed in many eye diseases, such as amblyopia and developmental dyslexia. The detection of pathological eye movement behaviour is difficult and requires more data for comparison. Therefore, the main purpose of this study was to evaluate the influence of age, school level, gender, and mother tongue on eye movements while reading.Methods One hundred and twenty-seven normally sighted children aged 7 – 12 were recruited from grades 2 – 5. The children were asked to read aloud two texts of The New International Reading Speed Text (IReST) of similar difficulty. Eye movements while reading were recorded by eyetracking technology (SMI RED 250, SensoMotoric Instruments, Teltow, Germany). The eye movement parameters were obtained from 118 children, and reading speed (words/minute), number of saccades, number of fixations, reading errors, and influence of school grade were analyzed.Results We showed a significant influence of age in all eye movement parameters. The main finding of this study is that younger children performed more saccades, a higher number of fixations per word, and more reading errors while taking more time to read the text than older children in higher grades. In early grades, non-native German speakers read more slowly and performed more saccades and fixations, but no more differences were seen by grade 5. Overall, there was no significant influence of gender or school system on reading parameters.Conclusion This study highlights the need for an age-appropriate normative database for eye movements during reading.
Keywords: IReST; eye tracker; eye movements; reading